Footwork technique used in elite table tennis matches - Ivan Malagoli Lanzoni; Michail Katsikadelis; Gunter Straub; Zoran Djokic (Universidad de Granada, 2019)
Notational and Match analysis are very well-recognized methods to collect information about the most common technical-tactical performance indicators in table tennis: footwork and stroke types. The aim of this study was to compare footwork distributions in men (M) and women (W) elite table tennis competitions. Nine men's and nine women's matches were analyzed. All players were in the top 120 (M) and 111 (W) positions of the ITTF world ranking. An expert coach analyzed game video recordings in slow motion with the software Kinovea and collected data about the footwork types used by the players during the games. The results showed differences between M and W: M prefer to use one step (35.6%, W: 21.9%), W prefer to hit the ball without performing any step (W: 40.2%, M: 20.4%), the chassé is equally used (M: 19.7%, W: 21.7%), and the crossover is mainly used by M (11.1%, W: 3.7%). The pivot is mainly used by M (9.9%, W: 7.8%), and W prefer the slide (4.9%, M: 3.2%). In conclusion, this study can be useful for physical trainers, performance analysts, and coaches, to design specific footwork training sessions for M and W elite table tennis players.